Analisis Tingkat Pemahaman Calon Pengantin Mengenai Konsep Keluarga Sakinah dalam Al-Qur’an di Kua Kecamatan Medan Area - Ariza, Fauziah Nur; Sari, Widya Puspita; Harahap, Siti Khoiriah; Suri, Reka; Hasibuan, Nafis; Bintang, Muhammad Arif Yasin; Fathansyah, Esha Daffa (Universitas Batanghari Jambi, 2026)
This study aims to analyse the understanding of prospective brides and grooms in the Medan Area Subdistrict KUA regarding the concept of the 'sakinah family' in the Qur'an, and the factors that influence it. The study employs a qualitative approach with a case study design. Data were collected by observing the premarital counselling service at the KUA and analysed descriptively and analytically. The results show that prospective brides and grooms' understanding of the sakinah family concept is still formalistic, focusing on administrative aspects and basic marriage laws. The values of sakinah, mawaddah and rahmah have not yet been fully embraced as the basis for creating a harmonious household. This limited understanding is influenced by the technical orientation of premarital counselling, which still predominantly emphasises legal and formal aspects. The study therefore emphasises the importance of strengthening the role of the KUA by providing more contextual and reflective premarital counselling to prepare prospective brides and grooms not only administratively, but also spiritually, psychologically and socially, to realise a sakinah family.